The Methodological Bases For Intellectual Games Aimed At The Formation Of Preschoolers’ Meta-Abilities - Panosyan, Anahit (Զանգակ հրատ.)
This article presents a comprehensive study of the methodological foundations that have been carried out on the selection of intellectual games, especially chess, aimed at developing meta-abilities in older preschool children. This research, conducted in the context of the Republic of Armenia, addresses a significant knowledge gap regarding the development of meta-abilities of preschool children, with particular emphasis on the use of game-based learning methodologies, particularly intellectual games. Based on the work of Bethel-Fox (1992), which clearly distinguishes types of meta-abilities, the study offers a solid methodological framework aimed at optimizing the selection of intellectual games, mainly focusing on the development of personal meta-abilities such as self-orientation and initiative (Brown R. B, 2002). During the research, the gaps and features related to the field were thoroughly studied, and specific methods of their correction were developed in the context of the selection of intellectual games. At the end of the research, theoretical analyses were presented with empirical evidence collected from experimental research in two groups of 5-6-year-olds. The first group comprised 20 children, and the second group comprised 6. The first group was in Hrazdan, and the second was in Yerevan. The article examines in detail the content, implementation strategies, and resulting outcomes of using Chess as a means of building meta-skills.
Keywords: Pedagogy; Psychology